2014
DOI: 10.3390/ijms150712061
|View full text |Cite
|
Sign up to set email alerts
|

Value of Micro-CT for Monitoring Spinal Microvascular Changes after Chronic Spinal Cord Compression

Abstract: Neurological degeneration can occur after compression of the spinal cord. It is widely accepted that spinal cord compression leads to ischemic lesions and ultimately neurological dysfunction due to a narrowed spinal canal. Therefore, an in-depth understanding of the pathogenesis of spinal cord compression injury is required to help develop effective clinical interventions. In the present study, we propose a new method of quantitative 3D micro-CT to observe microvascular events in a chronic spinal cord compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Previous research has reported that micro-CT could be used to analyze neurovascular pathology based on 3D vascular network patterns and features in an experimental rat acute spinal cord injury model [13]. In previous study, we also have found that 3D micro-CT is useful for investigating microvascular changes after chronic cervical spinal cord compression [11]. However, it has not yet used to study the quantitative analysis of ASA and ARA in chronic compressive model, which efficiently display the anatomical features and comprehensively evaluate injury of the ASA and ARA.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previous research has reported that micro-CT could be used to analyze neurovascular pathology based on 3D vascular network patterns and features in an experimental rat acute spinal cord injury model [13]. In previous study, we also have found that 3D micro-CT is useful for investigating microvascular changes after chronic cervical spinal cord compression [11]. However, it has not yet used to study the quantitative analysis of ASA and ARA in chronic compressive model, which efficiently display the anatomical features and comprehensively evaluate injury of the ASA and ARA.…”
Section: Discussionmentioning
confidence: 90%
“…Micro-CT can provide a clear visualized 3D image of microvascular network, ASA and ARA [11,13]. In this study, we shed new light on the spatial and temporal changes of ASA and ARA as the change of neural function.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Recently, various methods, including histopathology, confocal microscopy, magnetic resonance imaging (MRI) and computed tomography (CT), have been used to assess the spinal cord condition (Talbott et al, 2015;Long et al, 2014). Immunohistological analysis and confocal microscopy may achieve a higher resolution via the use of specific antibodies directed against tissues and cells (Dong et al, 2008;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%